Characterizing the spatiotemporal response of runoff to impervious surface dynamics across three highly urbanized cities in southern China from 2000 to 2017 - Kai Liu; Xueke Li; Shudong Wang (International Journal of Applied Earth Observations and Geoinformation, 2021)
Urbanization affects the regional hydrological cycle, but quantitative assessment of the hydrological regime in regions of high urbanization remains unexplored. This study investigates the response of runoff to impervious surface area (ISA) dynamics across three highly urbanized cities in southern China. The Soil Conservation Service Curve Number hydrologic model is modified by coupling the 1-km high-resolution calibrated precipitation data and 250-m-resolution percentages of remotely sensed land cover. Results demonstrate that runoff metrics increase noticeably during 2000–2017 at the city scale, with larger (smaller) magnitudes observed for high-flow (low-flow) runoff metrics. Runoff trend variations are more pronounced during high-flow seasons and are remarkable over land surfaces. Analyses of linear regression and generalized additive models indicate that ISA changes account for 23–27% of the total variance of increased runoff. The ascending trend of runoff is not affected substantially by the slight decrease in ISA during 2014–2017, which is attributed to the combined influence of land cover changes and climate. At the subwatershed scale, changes in ISA explain 17% of runoff variations. The runoff regime is more (less) responsive at the high (low) ISA percentage, and one threshold indicative of substantial modification to runoff is detected in the ISA percentage. Overall, runoff responses identified in the spatiotemporal analysis underscore the importance of monitoring and assessing the hydrological regime in southern China as urbanization progresses.